Effect of Row Spacing and Seeding Rate on Yield Component and Seed Yield of Alfalfa (Medicago sativa L.) - Gholamreza ABADOUZ; Abdollah HASANZADEH GORTTAPEH; Abdol Amir RAHNEMA; Adela BEHRADFAR (Notulae Scientia Biologicae, 2010)
In order to investigation the effect of row spacing and seeding rate on alfalfa (Medicago sativa L. cv. Mesasirsa) an experiment was carried out at the research farm of Khouzestan Agricultural Research Center from 2000 to 2004. This research was conducted in the form of a split plot design in a randomized complete block, with four replications. Main plot was three row spaces (50, 60 and 70 cm) and sub plots were five seeding rates (5, 10, 15, 20, and 25 kg seed ha-1). Results showed that the highest seed yield obtained in the second year. Seed yield and raceme per m2 increased with row spacing decreased. Seeding rate did not have any significant effect on pod per raceme, seed per pod and seed weight. The interaction of year and treatments on whole of traits were not significant. It was observed that correlation among seed yield and yield components was positive and significant. It was concluded that with using 15 kg seed ha-1 obtained highest seed yield due to increase in raceme per m2 and seed weight.